2020
DOI: 10.1097/fch.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Disorganization and Child-rearing Beliefs Toward Physical Punishment Among Asian American Parents

Abstract: Previous studies have indicated that neighborhood disorganization affects child-rearing beliefs in the United States, but few studies have focused on such influences among Asian American parents. Largely due to Asian American parents' immigration experiences, neighborhood disorganization factors inevitably intersect with their traditional cultures, which may lead to different patterns in their parental beliefs. Using structural equation modeling, this study found that neighborhood disorganization factors direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Norbeck presented a conceptual model regarding the mediating effect of stress between social support and health [23]. The mediating effects of acculturation stress and parenting stress among immigrant populations were found between mental health and social behavior, and between parents' beliefs and mental health, respectively [24,25]. Hence, the question "do acculturative stress and parenting stress play a moderating role in the relationship between social support and health among immigrant Chinese women in Japan?"…”
Section: Introductionmentioning
confidence: 99%
“…Norbeck presented a conceptual model regarding the mediating effect of stress between social support and health [23]. The mediating effects of acculturation stress and parenting stress among immigrant populations were found between mental health and social behavior, and between parents' beliefs and mental health, respectively [24,25]. Hence, the question "do acculturative stress and parenting stress play a moderating role in the relationship between social support and health among immigrant Chinese women in Japan?"…”
Section: Introductionmentioning
confidence: 99%
“…Poverty is a risk factor for the abuse or neglect of children because rates of child maltreatment are higher among families whose income falls below the poverty line (Waldfogel, 1998 ). Parents in economically disadvantaged communities had more positive attitudes toward using physical discipline (Pei et al, 2020 ). Compared to other forms of child maltreatment, parents’ socioeconomic status is negatively associated with child neglect (Petersen et al, 2014 ).…”
Section: Economic Hardshipmentioning
confidence: 99%
“…Standards concerning acceptable child-rearing and punishment vary by culture and may have evolved to reflect the necessities of the group. For example, Asian parents have typically used authoritarian parenting styles and corporal punishment (Hahm and Guterman, 2001 ; Pei et al, 2020 ). Several different factors, including environmental, stress, physical, social, intellectual, and emotional functioning of caregivers and children, provide conditions for individuals to move beyond culturally sanctioned levels of physical discipline (Gil, 2014 ).…”
Section: Child Maltreatment Among Asian American and Pacific Islander Familiesmentioning
confidence: 99%
“…Using Bronfenbrenner’s [ 19 ] ecological theory, predictive factors of parenting stress can be categorized as individual-, family-, and neighborhood-level factors. Research on neighborhood-level factors and parenting stress yielded inconsistent findings [ 5 , 20 , 21 ]. For example, McCloskey and Pei [ 20 ] suggested that neighborhood social cohesion had direct positive effects on maternal parenting stress; Wang et al [ 22 ] had similar findings that both neighborhood collective efficacy (positively) and poverty (negatively) affected parenting stress.…”
Section: Introductionmentioning
confidence: 99%